Characterization of Pseudomonas syringae pathovars from different sweet cherry cultivars by RAPD analysis - Iličić Renata (Genetika, 2016)
Pseudomonas syringae pvs., isolated from sweet cherry grown on different localities in Serbia, were genetically characterized using RAPD analysis. Four out of eleven tested primers (SPH1, DJP 17, DJ 15, and DJ 16) were selected on the basis of the differences between isolates within two pathovars - syringae and morsprunorum race 1. Cumulative RAPD analysis indicated heterogeneity within the population of both groups of tested isolates, revealing four different patterns in each group. RAPD analysis showed up to 24% differences among pv. syringae isolates, as well as 41% in comparison with the reference strain KFB0103 (pv. syringae), while differences of 15% among isolates pv. morsprunorum 1 race and 36% compared to the reference strain CFBP2119 (pv. morsprunorum 1) were observed. Isolates from locality Selenca exhibited three different genotypic patterns of pv. morsprunorum race 1 and one pattern of pv. syringae. Isolates of pv. morsprunorum collected in the same year from two plant organs (branches and leaves) of the cv. Vanda yielded two different patterns. The pv. morsprunorum on cv. Kordia and pv. syringae on cv. Regina were detected at Mikicevo locality. The same patterns were observed for isolates of pv. syringae from Kanjiza and Selenca, as well as from Gornji Tavankut in two years of isolation. Differences were noted between isolates from the same pathovar originating from Ljutovo and Mikicevo, as well as with respect to all other isolates of same pathovar. [Projekat Ministarstva nauke Republike Srbije, br. III46007]